2012
DOI: 10.1186/1475-2875-11-213
|View full text |Cite
|
Sign up to set email alerts
|

Entomologic investigation of Plasmodium knowlesi vectors in Kuala Lipis, Pahang, Malaysia

Abstract: BackgroundThe first natural infection of Plasmodium knowlesi in humans was recorded in 1965 in peninsular Malaysia. Extensive research was then conducted and it was postulated that it was a rare incident and that simian malaria will not be easily transmitted to humans. However, at the turn of the 21st century, knowlesi malaria was prevalent throughout Southeast Asia and is life threatening. Thus, a longitudinal study was initiated to determine the vectors, their seasonal variation and preference to humans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 34 publications
2
132
0
2
Order By: Relevance
“…Ideally parallel collections of mosquitoes attracted towards macaques would have been conducted but this was not possible due to logistical constraints and ethics regulations for working with macaques. Previous work [22, 23] showed that the P . knowlesi vectors in other areas namely An .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally parallel collections of mosquitoes attracted towards macaques would have been conducted but this was not possible due to logistical constraints and ethics regulations for working with macaques. Previous work [22, 23] showed that the P . knowlesi vectors in other areas namely An .…”
Section: Discussionmentioning
confidence: 99%
“…knowlesi make it particularly difficult to control by conventional methods: (1) it has a sizeable zoonotic reservoir in macaques, which means that even if infections are eliminated from humans there remains a risk of future spillover, and (2) current evidence indicates that previously incriminated mosquito vectors of P . knowlesi in Malaysia bite and rest outdoors where control methods such as LLINs and IRS will not be effective [19, 22, 23]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mosquito species feeds mainly between 7 and 10 p.m. in the forest, is attracted to both long-tailed macaques and humans, and prefers to feed on macaques at higher elevations. A. cracens has recently been incriminated as a vector for knowlesi malaria in Pahang, Peninsular Malaysia, with peak biting times between 8 and 9 p.m. (44,84). This species is highly zoophilic and was previously found to feed on macaques at the canopy level and on humans at the ground level.…”
Section: Vectorsmentioning
confidence: 99%
“…In Malaysian Borneo, the area with the most intense P. knowlesi transmission, several Anopheles species competent for monkey-tohuman transmission have been identified which predominantly feed between 7 and 10 p.m. [19][20][21]. Interestingly, P. knowlesi alone but also together with P. vivax and/or P. falciparum has been isolated from saliva glands of Anopheles dirus in southern Vietnam [22].…”
Section: Introductionmentioning
confidence: 95%